O celular na escola: desafios nas aulas de Língua Portuguesa - Grossi, Rafaela Thais Gomes (2020)
This study aims to present and analyze ideas related to technologies in the field of education, as well as the cell phone use, as a mobile device, in activities in Portuguese language classes. For this purpose, a bibliographic research was carried out to support the discussion, in addition to field research, with interviews with two education professionals and observation of classes. Based on authors such as Kenski (2012), Moran (2018), Rojo (2012), Coscarelli (2017) and Mizukami (1986), among others, we were able to deepen knowledge about the conceptions about technology and information and communication technologies, as well as the educational area and its teaching approaches. Both theories and understandings arising from the data collected in the field led us to more reflective analyzes of the observed reality, paying attention to material, structural, technological and conducting aspects of Portuguese language classes, in contexts of cell phone use by students. Thus, the results led us to conclude that the referred mobile device can be of great use in pedagogical activities and that its use requires essential prior care, such as planning and clear objectives that guide the work of the teacher with students. Anyway, because it is the field of education, where many variables are at stake, we intend to contribute to the discussions that already exist in the area.